Peltaster fructicola genome reveals evolution from an invasive phytopathogen to an ectophytic parasite - Xu, Chao (Sci Rep, 2016)
Sooty blotch and flyspeck (SBFS) fungi are unconventional plant pathogens that cause economic losses by blemishing the surface appearance of infected fruit. Here, we introduce the 18.14-Mb genome of Peltaster fructicola, one of the most prevalent SBFS species on apple. This undersized assembly contains only 8,334 predicted protein-coding genes and a very small repertoire of repetitive elements. Phylogenomics and comparative genomics revealed that P. fructicola had undergone a reductive evolution, during which the numbers of orphan genes and genes involved in plant cell wall degradation, secondary metabolism, and secreted peptidases and effectors were drastically reduced. In contrast, the genes controlling 1,8-dihydroxynaphthalene (DHN)-melanin biosynthesis and appressorium-mediated penetration were retained substantially. Additionally, microscopic examination of the surfaces of infected apple indicated for the first time that P. fructicola can not only dissolve epicuticular waxes but also partially penetrate the cuticle proper. Our findings indicate that genome contraction, characterized mainly by the massive loss of pathogenicity-related genes, has played an important role in the evolution of P. fructicola (and by implication other SBFS species) from a plant-penetrating ancestor to a non-invasive ectophyte, displaying a novel form of trophic interaction between plants and fungi.